Biomechanical and physiological responses to 120 min. of soccer-specific exercise - Field, A.; Corr, L. D.; Haines, M.; Lui, S.; Naughton, R.; Page, M.; Harper, L. M. (Research Quarterly for Exercise and Sport, 2020)
Purpose: The purpose of the study is to investigate biomechanical and physiological responses to soccer-specific exercise incorporating an extra-time period (ET) and assess the test-retest reliability of these responses. Methods: Twelve soccer players performed 120 min of soccer-specific exercise. Tri-axial (PLTotal) and uni-axial PlayerLoad™ in the vertical (PLV), anterior-posterior (PLA-P), and medial-lateral (PLM-L) planes were monitored using a portable accelerometer. Likewise, respiratory exchange ratio (RER) was recorded throughout exercise. At the end of each 15-min period, players provided differential ratings of perceived exertion for legs (RPE-L), breathlessness (RPE-B) and overall (RPE-O), and capillary samples were taken to measure blood lactate (BLa) concentrations. The soccer-specific exercise was completed twice within 7 days to assess reliability. Results: A main effect for time was identified for PLTotal (p = 0.045), PLV (p = 0.002), PLA-P (p = 0.011), RER (p = 0.001), RPE-L (p = 0.001), RPE-O (p = 0.003), and CMJ (p = 0.020). A significant increase in PLTotal (234 ± 34 au) and decrease in RER (0.87 ± 0.03) was evident during 105-120 versus 0-15 min (215 ± 25 au; p = 0.002 and 0.92 ± 0.02; p = 0.001). Coefficients of variations were <10% and Pearson`s correlation coefficient demonstrated moderate-to-very strong (0.33-0.99) reliability for all PL variables, RPE-B, BLa, and RER. Conclusions: These results suggest that mechanical efficiency is compromised and an increased rate of lipolysis is observed as a function of exercise duration, particularly during ET. These data have implications for practitioners interested in fatigue-induced changes during ET.